Терракоты из Тарента в коллекции Одесского археологического музея - Савельева, Е.С. (Материалы по археологии Северного Причерноморья, 2015)
Fourteen terracotta sculptures of Tarentum presented to Odessa Archaeological Museum in 1900 have been published in the article. The sculptures are divided into several plot-line groups, as well as into two chronological periods. The first period (V–IV Centuries A.D.) comprises the images of Dionysus reclining, Artemis Bendis, Demeter and a comical actor. Images of a woman and a child with goose, as well as votive women’s heads, belong to the second period (III–II Centuries B.C.).